(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to evaluate the safety and validity of the ESI risk classification model already used in the emergency care service of a ready care unit 24 hours of Canoas/RS for children under 18 years of age. Method: For this, a quantitative research was applied, with an analytical approach, which was divided into two phases, the first in the data collection in the service bulletins, and the second in the test with the internal and external nurses to the service. We analyzed the level of classification attributed in each care, resource consumption, length of stay in the service, transfer to hospitalization and death. Results: They showed weaknesses in the application of the risk classification, with elevation of the classification level in relation to the posterior medical procedure. There were also discrepancies in the classification of the same case by different nurses. Conclusion: The evaluation of the data results in the contribution to improve the knowledge and skills of the nurses in the use of the scale, in addition to qualifying the work process and conferring benefits to the user.